The Financial and Workforce Impact of Medication Errors in the Finnish Public Healthcare System: A Pilot Study - Kanninen, Jonna-Carita; Ojala, Raimo; Ahonen, Jouni; Kautiainen, Hannu; Holm, Anu; Valkonen, Ville (SAGE Publications, 2026)
Background
Medication errors (MEs) pose a significant challenge to patient safety and healthcare efficiency. In addition to clinical consequences, MEs contribute to increased healthcare expenditures and resource utilization. However, comprehensive cost assessments of MEs, including staff time and service costs, remain limited.
Objectives
The aim of this pilot study is to examine the costs associated with MEs regionally and nationally in Finland.
Design
Cross-sectional study.
Methods
This study assessed the financial and resource burden of MEs in the Finnish public healthcare system using a survey conducted in the wellbeing services county of North Savo in Eastern Finland. The study perspective is economic and healthcare system-focused. Healthcare professionals in charge of patient safety reporting estimated the workforce impact of MEs by assessing the time spent, the corrective measures taken, and the additional interventions required to manage these events. Cost calculations were based on salary data from the 2023 financial administration statistics and service costs from the Finnish Institute for Health and Welfare (THL) database, adjusted to 2023 monetary value. An estimator, derived from regional data, was applied to extrapolate the nationwide economic burden of MEs.
Results
Medication errors (MEs) impose a substantial financial burden, with an estimated mean cost of €138 per event and a total annual cost of €686 274 in the wellbeing services county of North Savo. Extrapolated to the national level, the annual impact was estimated at €15.5 million. The main cost drivers were the work time expenditures of nurses and physicians involved in managing these events.
Conclusion
Managing MEs demands extra work of healthcare personnel, which is a considerable waste of resources. Most of the events are preventable. That is why effective safety strategies are needed, and prompt action taken to improve quality of care and reduce unnecessary costs.